A critical analysis of the taxation of income arising to contractors in relation to the execution of engineering, procurement, construction and installation (‘EPCI') contracts in the oil and gas sector - Smith, Shirlynn (Department of Finance and Tax, 2021)
Globally, the past two years have been successful years in oil and gas exploration with discoveries almost doubling those made in 2017.1 Notwithstanding Africa's endowment in vast natural resources, including substantial oil and gas reserves, one of the most dramatic finds in Africa has been Mozambique's natural gas developments. Mozambique is set to become one of the largest and most dominant natural gas finds in the world. These developments have attracted the attention from countries around the world, the UAE, in particular, taking the lead. Engineering, procurement, construction and installation (“EPCI”) contracts, are a common form of contract in the oil and gas sector, which is used to undertake large scale oil and gas projects. The nature of these contracts consists of significant local (in-country work) and foreign (out-of-country work) elements. Due to the complex nature of EPCI contracts, one of the major areas of dispute in the taxation environment are the uncertainties around the taxation of profits arising to contractors under these contracts. The taxpayer and the Revenue Authorities have different views as to where the income arising from EPCI contracts is to be taxed. The taxpayer takes the stand that only such income from the project as is relatable to activities in the host state, should be taxed in the host state. The Revenue Authorities contend that EPCI contracts are to be considered as one and indivisible, and hence the entire income from the contract is liable to be taxed in the host state. Based on an examination of recent judgments passed by the Authority of Advanced Rulings (“AAR”) and various Tax Courts, currently, there seems to be no certainty regarding the taxation of income arising to contractors under an EPCI contract and this has in turn resulted in a number of contractors having to pay excessive taxes. This dissertation seeks to analyse the tax treatment of income arising to contractors, from supplies and services under an EPCI contract in the context of the oil and gas sector entered into between Mozambique and the United Arab Emirates (“UAE”), in Mozambique. The purpose of this analysis is to determine how these profits should be taxed, in light of the Mozambique-UAE Treaty2 and Mozambican domestic legislation. In other words, the question that this dissertation seeks to answer is, whether profits arising from an EPCI contract in the oil and gas sector, should be taxed as a whole in Mozambique, or per the various components of the EPCI contract. 1 Fuel for thought, Africa oil and gas review, 2019, Current developments and a look into the future, www.pwc.co.za/oil-gas review [November 2019]. 2 Convention between the Republic of Mozambique and the Government of the United Arab Emirates for the Avoidance of Double Taxation with respect to Taxes on Income and Capital (2003). The key finding arising from the research presented in this dissertation is that although an EPCI contract is entered into in Mozambique (consisting of both offshore and onshore elements), this would not make the entire income from that contract to be taxable in Mozambique. Importantly, only such part of the income as is attributable to the operations carried out in Mozambique can be taxed in Mozambique. Following the analysis, as described above, this dissertation finally endeavors to provide recommendations on how contractors should approach and structure EPCI arrangements in order to create the best possible situation for themselves within the limits of what the law allows, and to reduce potential tax litigation. This can serve to inform other developing countries who have oil and gas operations.